DIAGNOSIS OF LEARNING DIFFICULTIES IN MATHEMATICS (GEOMETRY) FOR STUDENTS GRADE X AT SMK NEGERI 3 YOGYAKARTA - Shella Azizah; Sahid . (Jurnal Pedagogi Matematika, 2017)
The  objectives  of  this  research  are  to  describe  the  difficulties  of  students  and  their  causes  in solving geometry problems. The difficulties were observed related to the concept and principles.This  research  is  a  qualitative  research  with  case  study  strategy.  Subjects  of  this  research  are seven students of class X KR 1 and X TP 2 at SMK Negeri 3 Yogyakarta whom diagnosed have learning difficulties in solving geometry problems. Qualitative data were collected by test and interviews. The data were analyzed descriptively qualitative.The results show the concept of geometry that has not understood by students are the concept of solid geometry (cubes and rectangular prism), right triangle, the projection (the point on the line, the point on the plane, and the line on the plane), perpendicular concept (two lines, lines and plane), distance (point to  the  line,  point  to  the  plane  and  two  parallel  planes),  and  angle  (lines  and  plane,  two  planes). Meanwhile, the principle of which is not mastered by students are the principle of projection, distance calculations,  the  Pythagorean  theorem,  calculation  of  the  root,  the  calculation  of  the  angle  and trigonometry  comparison.  The  cause  of  the  learning  difficulties  by  students  is  students  do  not  have awareness to learn regularly.